Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

L'offre active de services de santé en français en Ontario: Une mesure d'équité. Rapport préparé pour le Bureau des services en français du Ministère de la Santé et des Soins de longue durée de l'Ontario. Réseau de recherche appliqué sur la santé des francophones de l’Ontario (RRASFO) - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (2011)
Le présent rapport fait état d’une première étape d’une recherche sur l’offre active de services en français (SEF) en Ontario. L’étude a été effectuée dans le cadre de l’entente Canada-Ontario sur les services en français pour le Bureau des services de santé en français du MSSLD. Elle a pour objectifs de recenser les définitions de l’offre active de SEF; d'identifier les pratiques d’offre active (facilitateurs et/ou obstacles); d'identifier les indicateurs de mesure de l’offre active; de proposer des recommandations permettant d’améliorer l’offre active de SEF. En raison des limites imparties en terme de temps et de moyens, cette étude s’est limitée à préciser les pourtours du concept d’offre active et de ses modalités d’application, en privilégiant: a) une revue documentaire; b) une enquête auprès du premier groupe de professionnels attitrés à la fonction de coordination régionale des services de santé en français, les coordonnateurs aux SEF des actuels RLISS, au moyen d’un questionnaire autoadministré et c) un atelier de cartographie conceptuelle, une méthode de recherche participative. L'étude n’a pas la prétention de brosser le portrait global de la situation des services de santé en français, ni d'évaluer les politiques antérieurement adoptées telle que la désignation des SEF, non plus que de faire office de consultation générale sur le thème. Cette première étape de recherche sur l’offre active, ses méthodes et ses outils, démontre qu’il s’agit là d’un concept clé en matière de services de santé en français qui peut contrer les effets de la minorisation des francophones et améliorer les services en français.

« Dialogue santé » une consultation historique auprès des communautés francophones de l’Ontario - Dallaire, Hélène; Rail, Geneviève (Reflets, 1995)

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)

Profil statistique 2011 – Personnes âgées francophones du Canada - Fédération des aînées et aînés francophones du Canada (2014)

Le cours d’été en promotion de la santé, session 1999 - Fraser, Colette (1999)
Introduction: Depuis longtemps, on parle de l’importance de former les formatrices et les formateurs dans le domaine de la santé. Or, le Cours d’été en promotion de la santé (CÉPS) cherche justement à répondre à ce besoin depuis bientôt six ans dans la province de l’Ontario. Le ministère de la Santé de l’Ontario et le Centre for Health Promotion de l’Université de Toronto parrainent ce projet depuis ses débuts. Pourtant, l’étendue de cette expérience éducative dépasse largement le cadre et l’enceinte de l’institution universitaire. Cela s’est avéré particulièrement vrai lors de l’édition 1999 du cours d’été qui a lieu à l’Université Laurentienne de Sudbury du 31 mai au 3 juin. En plus d’avoir lieu dans le Nord de l’Ontario pour la première fois, ce cours d’été comportait trois volets culturels, soit les volets anglophone, francophone et autochtone. Conclusion: Le CÉPS continuera dans le nouveau millénaire à être un outil d’apprentissage pour ceux et celles qui s’intéressent à la promotion de la santé. Selon les évaluations des participantes et participants, il s’agit d’une activité à fortement recommander. Dans l’avenir, les individus choisiront la santé comme faisant partie intégrante de leur vie. Pour ceux et celles qui choisissent de le faire en français, il faudra veiller à constituer, dans le cadre du CÉPS, un volet francophone fort dans les années à venir. Pour nous en convaincre, rappelons en terminant les propos de Mauril Bélanger, secrétaire parlementaire de Patrimoine canadien, qui soulignait l’importance « de former des professionnels de la santé en français pour assurer à la population francophone des soins de santé dans sa langue »

A guide for Planning and Providing Francophone Long-term Care Services - Learning from Pavillon Omer Deslauriers (POD) at Bendale Acres and Other Franch Language Health Services for Seniors in Canada - FRENCH HEALTH NETWORK OF CENTRAL SOUTHWESTERN ONTARIO (2017)

Occupational Integration in Healthcare by French-speaking Immigrants Living in Minority Communities - Goss Gilroy Inc. (GGI) (2020)
This report presents the results of a research project on the occupational integration of French speaking immigrants in healthcare, in Francophone minority communities. Through interviews, this project examines the challenges faced by French-speaking immigrants working or pursuing a career in the health sector in Nova Scotia, Ontario and Alberta. Researchers also mobilized literature on the occupational integration of immigrants, data from the 2016 Census and the results of quantitative studies. The research shows that the need for English language skills constitutes a major obstacle at various stages of French-speaking immigrants’ occupational integration journey. The interviews also indicate that employment assistance services in French are not equipped to deal with the complex trajectories of internationally educated health professionals, or to help them identify alternative careers. During internships or at the start of employment, supports in French promoting the integration of immigrants (through mentoring, training workshops for employers, etc.) are very limited. Recommendations are addressed to the Department of Immigration, Refugees and Citizenship Canada and aim to improve supports offered to the study population from the start of their migration project to retention in their workplace.

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

HR Support Kit – Pathway to Bilingual services - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Les services en français, un facteur de qualité -Argumentaire et cadre d’analyse d’impact à l’attention des Réseaux locaux d’intégration des services de santé (RLISS) et des fournisseurs de services de santé (FSS) de l’Est et du Sud-Est de l’Ontario - Réseau des services de santé en français de l’Est de l’Ontario (2012)
Le document Les services en français, un facteur de qualité des services de santé élaboré par le Réseau des services de santé en français de l’Est de l’Ontario (le Réseau) a pour objectif de : - sensibiliser et informer des impacts de la barrière linguistique sur la qualité des services de santé en français et donc sur l’amélioration de l’état de santé de la population francophone; -véhiculer l’importance d’une planification de projets et d’initiatives en santé qui tiennent compte des barrières linguistiques afin d’améliorer l’état de santé de la communauté francophone vivant en contexte minoritaire. Pour ce faire, le Réseau a développé un argumentaire et un cadre d’analyse d’impact de la barrière linguistique, ayant pour appellation la lentille francophone, à l’attention des réseaux locaux d’intégration des services de santé (RLISS) et des fournisseurs de services de santé (FSS) des régions de Champlain et du Sud-Est.

Implementing the Optimal Model of Long-Term Care for Francophones and Other Cultural and Linguistic Minority Groups - Réseau franco-santé du Sud de l'Ontario and partners (2019)

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

Improving the active offer of french language services - Savard, Jacinthe; Sauvé-Schenk, Katrine (Société Santé en français, 2020)

Webinaire : Conditions gagnantes pour augmenter l'offre active efficace - Savard, Jacinthe; Sauvé-Schenk, Katrine (2019)

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.